The mask you live in (Kanopy Streaming, 2015)
HE MASK YOU LIVE IN follows boys and young men as they struggle to stay true to themselves while negotiating America’s narrow definition of masculinity. Pressured by the media, their peer group, and even the adults in their lives, our protagonists confront messages encouraging them to disconnect from their emotions, devalue authentic friendships, objectify and degrade women, and resolve conflicts through violence. These gender stereotypes interconnect with race, class, and circumstance, creating a maze of identity issues boys and young men must navigate to become “real” men. Experts in neuroscience, psychology, sociology, sports, education, and media also weigh in, offering empirical evidence of the “boy crisis” and tactics to combat it. The Mask You Live In ultimately illustrates how we, as a society, can raise a healthier generation of boys and young men.
Place: San Francisco, California, USA
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cinéma; communication; cours; discipline; documentaire; féminisme pop; histoire et politique; intersectionnalité; masculinité; premier cycle; périodes historiques; représentation des hommes; régions géographiques; sex2283; sexualité; thématiques; travail; violences; états-unis

Surname Viet given name Nam - Trinh, T. Minh-Ha (Thi Minh-Ha) (Women Make Movies, 1989)
Un essai sur la répression des femmes dans la société vietnamienne. Le film est centré sur la culture vietnamienne vue au travers de l'histoire de résistance des femmes, la tradition orale, les images encouragées par les medias ainsi que la vie et les regards des femmes vietnamiennes.
Directors: _:n21115 https://banq.kanopy.com/node/239200
Keywords: approches et analyses; asie; cours; fem3200; histoire et politique; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; vietnam